2013
DOI: 10.2174/1574891x113089990036
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum: A Potential for Biotechnological Production of Anti-Cancer and Immunomodulatory Drugs

Abstract: Based on the analysis of more than 270 patents and scientific articles, this state-of-the-art review presents Ganoderma lucidum, a medicinal basidiomycete mushroom with immunomodulatory and anti-cancer effects. Cultivation methods for the commercial production of G. lucidum fruit bodies and mycelia are summarized, with main active compounds of triterpenoids, polysaccharides, and proteins, often found in forms of proteoglycans or glycopeptides. Pharmacological effects with emphasis on anti-cancer and immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 0 publications
0
69
0
2
Order By: Relevance
“…Due to their significant medicinal importance, mushrooms of the Ganoderma species have gained noticeable interest from biomedical researchers. A number of studies have revealed the medicinal values of Ganoderma mushrooms against various life-threatening diseases and health complications like cancer, immunodeficiency, cardiovascular complications, diabetes, hepatic disease, neurodegeneration, and infectious disease (Hajjaj et al, 2005;Paterson, 2006;Ma et al, 2011;Chu et al, 2012;Tie et al, 2012;Xiao et al, 2012;Boh, 2013;Wang et al, 2013;Wu et al, 2013;Yue et al, 2013). There are numerous variations in the size, shape, and color of Ganoderma mushrooms, and they differ in biological properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their significant medicinal importance, mushrooms of the Ganoderma species have gained noticeable interest from biomedical researchers. A number of studies have revealed the medicinal values of Ganoderma mushrooms against various life-threatening diseases and health complications like cancer, immunodeficiency, cardiovascular complications, diabetes, hepatic disease, neurodegeneration, and infectious disease (Hajjaj et al, 2005;Paterson, 2006;Ma et al, 2011;Chu et al, 2012;Tie et al, 2012;Xiao et al, 2012;Boh, 2013;Wang et al, 2013;Wu et al, 2013;Yue et al, 2013). There are numerous variations in the size, shape, and color of Ganoderma mushrooms, and they differ in biological properties as well.…”
Section: Introductionmentioning
confidence: 99%
“…This mushroom, as a traditional oriental medicine, has been widely used as a tonic in promoting longevity and health for thousands of years in Asian countries including China, Japan and Korea 23) . The pharmacological activities of Ganoderma lucidum, especially its intrinsic immunomodulating, and anti-tumor properties, have been well documented extensively 24) . Ganoderma lucidum has been shown to have anti-cancer, immunomodulatory and immunotherapeutic effects 14) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…17 According to the latest laboratory and preclinical studies both in vitro and in vivo, the promising anticancer activity of G. lucidum can be attributed to a variety of different mechanisms. 18 …”
Section: Laboratory and Preclinical Studiesmentioning
confidence: 99%